The impact of the walking dead video game on students' reading comprehension on narrative text - Muhammad Husnun Nadhif (Journal of Research on English and Language Learning (J-REaLL), 2021)
With the development of technology every time, the development of media for learning is also overgrowing. Many new media are popping up especially digital-based media, ranging from images, audio, and video. All of that media has been widely used by teachers to get students excited about what they will learn in class. However, the longer these media feel boring for students, the teachers also have to twist their brains to find new media, one of which is video games. Several studies have looked into the influence of adventure video games on learning English; however, few studies have looked into the effect of adventure games on learning English. This study aimed to see how video games affected students' reading comprehension of narrative text. The study consisted of 50 students from SMA Negeri 1 Kebomas Gresik in tenth grade. X-IPS 1 and X-IPS 2 were the class examples. The impact of video games can be reflected in the multiple-choice scores of students. The author used a quantitative procedure and quasi-experimental design as the analysis methodology with a purposive sampling approach. A multiple-choice test was used as the testing tool. The findings in this study explain that video games do not significantly impact students but only increase the motivation of students to learn and entertain students only